An Unlikely Coronavirus Reinfection with Devastating Consequences: Interpreting Dynamic SARS-CoV-2 Test Result Through a Case Report - Mendes, João; Mendes dos Santos, Cristina; Rui Salvador, Mário; Lima, Carla; Cardoso, Joana; Almeida, Isabela (Gazeta Médica, 2022)
A 40-year-old woman was admitted to hospital with fever and cough during the pandemic of COVID-19. Past medical was notable for advanced chronic kidney disease. On admission, nucleic acid testing of a nasopharyngeal swab was positive for SARS-CoV-2. After 11 days she was considered cure with two negative tests in a row. Eight weeks later, she was going to receive a kidney transplant from a deceased donor, but she was tested again for SARS-CoV-2 and the result came out positive. After that, surgery was cancelled. In our opinion, this test should not have been performed. Through this case we overview the knowledge about infectivity, reinfection and reactivation of SARS-CoV-2. We believe who has been considered cured in the last three months should undertake immunosuppression treatment in case of transplant or cancer treatment. In these cases, benefits outweigh the eventual risks for most patients.